A conceptual study on investment-linked takaful product: protecting life and wealth for family institution - Abdul Aziz, Mariam; Redzuan, Nur Harena; Zakariyah, Habeebullah (2020)
The variety of products offered by financial institutions could overwhelm indi-viduals in their decision making. For financially savvy people, decision making is easier, but some do need guidance. Therefore, this research aims to assess the Shariah-compliant investment-linked plan takaful product that can help investors in choosing an alternative plan. An investment-linked takaful is a family takaful plan that combines investment and takaful cover. This product offers participants the freedom to choose the type and amount of takaful on the protection they need as well as the freedom to invest based on their risk appetite, financial objectives and the length of time they are willing to invest. The study also discusses the wealth protection and financial investment based on maqasid Shariah with relating to family institutions. The study would assist the individual in their invest-ment decision since this study provides information and prior knowledge to them to make an informed decision of a better takaful plan which complies with Islamic law. Besides, the undertaken research enables the public, investors, participants, and other stakeholders for a better understanding of nature, features, and structures associated with the invest-ment-linked takaful product.